2021
DOI: 10.1002/adma.202105947
|View full text |Cite
|
Sign up to set email alerts
|

Engineering d‐p Orbital Hybridization in Single‐Atom Metal‐Embedded Three‐Dimensional Electrodes for Li–S Batteries

Abstract: Li-S) batteries is seriously restricted by their low sulfur loading and utilization, sluggish reaction kinetics, and poor cycling stability. [4,5] So far, appropriate active adsorption [6,7] and catalytic centers, such as metal sulfides, [8][9][10] oxides, [11][12][13] nitrides, [14] and vanadium compounds, [15] have been introduced to enhance the sulfur utilization and accelerate the reversible conversion between lithium polysulfides (LiPSs) and Li 2 S. [16,17] However, high weight percentages of these additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
199
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(200 citation statements)
references
References 52 publications
1
199
0
Order By: Relevance
“…Therefore, the weakened Li–S bond reflects the catalytic effect of the sulfur redox catalysts. 63 Crystal Occupation Hamiltonian Population (COHP) analysis of the Li–S bond was performed to demonstrate the hybridization scenarios in Li 2 S, and the bond strength of the Li–S bond was quantitatively evaluated by the integrated-COHP (−ICOHP) value. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the weakened Li–S bond reflects the catalytic effect of the sulfur redox catalysts. 63 Crystal Occupation Hamiltonian Population (COHP) analysis of the Li–S bond was performed to demonstrate the hybridization scenarios in Li 2 S, and the bond strength of the Li–S bond was quantitatively evaluated by the integrated-COHP (−ICOHP) value. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…, Fe, Co, V)-based single atom catalysts. 28,62,63 The discrepancy in the cycling stability is essentially ascribed to the synergic effects of the strong adsorption ability and catalytic activity of the Sn–N 4 sites towards polysulfides. The chemical tethering of the polysulfides cannot necessarily lead into good capacity retention because the charge storage capacity can only be achieved through highly reversible electrochemical sulfur redox.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates the active sites of C@COF surface could guide the radical Li 2 S growth and the surface passivation can be avoided. [54,55] when using the CNTs, Li 2 S growth shows a tendency to 2DI model, which formed a uniform Li 2 S nucleation and made its surface easily passivated. [52] The Li 2 S dissolution kinetics was also evaluated.…”
Section: Characterizations Of C@cofmentioning
confidence: 99%
“…The FJK framework is general enough to be applicable to situations where magnitude of a complicated process can be estimated with a relatively simple orbitalbased descriptor. 69,70 Further applications were beyond the scope of this work and are part of future work. At the same time, we observed that for a poor choice of a Slater determinant pair representing the change of electronic structure FJK may be less accurate than conventional representations, as exemplified by QM7b's first excitation energies.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%